Low molecular weight heparin calcium sequential rivaroxaban for the treatment of cerebral venous sinus thrombosis and cortical venous infarction in children with nephrotic syndrome: case report - Zhang, Xiumin; Yang, Juan; Guo, Cuicui; Wang, Jingcai (Frontiers in Pediatrics, 2025)
Cerebral venous sinus thrombosis (CVST), though exceedingly rare, represents a serious complication in pediatric patients with nephrotic syndrome (NS). We describe an 11-year-old male with steroid-resistant nephrotic syndrome (SRNS) maintained on prednisone/tacrolimus therapy who subsequently developed CVST. The patient manifested respiratory/gastrointestinal symptoms (cough, diarrhea) followed by neurologic deterioration featuring headache, seizures, and altered consciousness. Magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) confirmed transverse sinus thrombosis with cortical venous infarction. A 5-day course of low-molecular-weight heparin (LMWH) followed by rivaroxaban achieved safe thrombus resolution, supporting this anticoagulation protocol in pediatric NS.